Single-nucleotide polymorphism analysis accurately predicts multiple impairments in hippocampal activity and memory performance in a murine model of idiopathic autism - Isabel Barón-Mendoza; Luis A. Márquez; Aliesha González Arenas; Jessica Guzmán-Condado; Vladimir A. Martínez-Rojas; Johaly Anguiano-Buenfil; Montserrat Mejía-Hernández; Jorge Luis Almazán; Leonor Pérez-Martínez; Gustavo Pedraza-Alva; Emilio J. Galván; Angélica Zepeda (Scientific Reports)
Abstract Autism spectrum disorder (ASD) comprises alterations in brain anatomy and physiology that ultimately affect information processing and behavior. In most cases, autism is considered idiopathic, involving alterations in numerous genes whose functions are not extensively documented. We evaluated the C58/J mouse strain as an idiopathic model of ASD, emphasizing synaptic transmission as the basis of information processing. Through in silico analysis, we found that the C58/J strain carries single nucleotide polymorphisms (SNPs) compared to the C57BL/6J control strain related to synaptic structure and LTP induction. These SNPs have human orthologs previously associated with ASD. We then assessed chemical potentiation (cLTP) in synaptosomes, the electrophysiological properties of hippocampal CA3 cells, and the induction of LTP in ex-vivo slices. An increased proportion of synaptosomes expressing the GluA1 subunit of AMPA receptor and Nrx1β in the membrane was found in the C57BL/6J control strain, but not in C58/J mice, after cLTP induction. Additionally, several electrophysiological properties of CA3 pyramidal cells and hippocampal communication were altered. Behaviorally, C58/J mice exhibited hyperactivity and subtle memory changes. Our results demonstrate that an idiopathic model of ASD exhibits alterations in hippocampal physiology from the cellular to the circuitry and behavioral levels.